Cover Picture: Biotechnology Journal 7/2017. Issue 7 (July 2017) - Unknown
Abstract: This special issue edited by Professors Guilherme N.M. Ferrera and Jarka Glassey includes the best research presented at the European Symposium on Biochemical Engineering Sciences (ESBES), ranging from bioeconomy and sustainability, solvent free extractions, new biocatalysts and biotherapeuticals, as well as bioprocess control and design based on modeling and predictive tools. The cover picture shows a bridge of Dublin where the congress took place in September 2016. Abstract : This special issue edited by Professors Guilherme N.M. Ferrera and Jarka Glassey includes the best research presented at the European Symposium on Biochemical Engineering Sciences (ESBES), ranging from bioeconomy and sustainability, solvent free extractions, new biocatalysts and biotherapeuticals, as well as bioprocess control and design based on modeling and predictive tools. The cover picture shows a bridge of Dublin where the congress took place in September 2016.